Penentuan Kadar Bleaching Earth dan Phosporic Acid Pada Proses Degumming dan Bleaching Crude Palm Oil - Wira Irawan Rossani; Bahruddin; Amun Amri (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2021)
Oil from palm oil processing into crude palm oil generally still contains impurities, so it is necessary to carry out a physical refining process which includes pre-treatment and deodorization processes consisting of degumming and bleaching processes to remove gum and other impurity components. The purpose of this study was to determine the ratio of phosphoric acid in the degumming process using phosphoric acid and the bleaching process using bleaching earth on the quality of crude palm oil and degumm bleach palm oil. The degumming treatment used phosphoric acid with several concentrations, namely 0.5% and 1%, which was compared with the control using bleaching earth with the percentage of use 0%, 0.5%, 1%, 1.5% and 2% (crude palm oil before degumming process and after degumming process). Analysis of crude palm oil quality includes free fatty acid (FFA), DOBI, peroxide value (BP), phosphorus content, water content, and iron content of crude palm oil and DBPO. The results of this study indicate that the process after degumming using phosphoric acid at a concentration of 0.5% produces ffa 2.01-3.30 %), DOBI (1.55-2.13), PV (0-1.64mg O2/100mg ), phosphorus (3.76-11.01 ppm), water content (0.21-0.43), iron content (0.17-0.54) . The degumming process using 1.0% phosphoric acid produces ffa 1.65-3.59 %), DOBI (1.68-1.91), PV (0-2.54mg O2/100mg), Phosphorus (2.24- 15.41ppm), water content (0.24-0.88), iron content (0.11-0.61). Which is effective for saving production costs in the treatment with 0.5% phosphoric acid concentration and the use of 1% bleaching earth.